1997
DOI: 10.1002/chin.199739186
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis, Characterization and CNS Activity of Some Novel Piperazine Derivatives.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…According to other literature, 9 added AcOH will prompt the formation bond of C=N. Contrarily in our work, the guanidinohydrazones can be only obtained in the absence of AcOH and the condensation of glucosyl-aminoguanidines with 3-formylchromone proceed rapidly in boiling THF in a higher yield.…”
Section: Resultsmentioning
confidence: 68%
“…According to other literature, 9 added AcOH will prompt the formation bond of C=N. Contrarily in our work, the guanidinohydrazones can be only obtained in the absence of AcOH and the condensation of glucosyl-aminoguanidines with 3-formylchromone proceed rapidly in boiling THF in a higher yield.…”
Section: Resultsmentioning
confidence: 68%
“…[11] It involves the reaction of 2-aminopyridine, salicylaldehyde and ethyl isocyanoacetate, and is catalyzed by scandium triflate to afford 3-aminoimidazoA C H T U N G T R E N N U N G [1,2-a]pyridines in good yields (> 80%). However, we accidentally found that by using CuA C H T U N G T R E N N U N G (OTf) 2 as catalyst in this reaction, one strong fluorescent spot was observed in thin layer chromatography (TLC) analysis. Single crystal X-ray diffraction analysis then showed this compound to be 3-formamidocoumarin (Figure 1), obtained in 33% yield (entry 1, Table 1).…”
mentioning
confidence: 94%
“…Coumarin and its derivatives occur widely in medicinal chemistry, and are considered to be "privileged structures" in the pharmaceutical and agrochemical industries. [1] A particularly interesting group of coumarins is 3-aminocoumarins, since they are used as CNS depressant, [2] antitumor, [3] anti-inflammatory, [4] and antimicrobial agents. [5] In addition, these compounds are also known to exhibit interesting photochemical behavior and have been used as fluorescent markers.…”
mentioning
confidence: 99%
“…A large number of substituted imidazo [1,2-a]pyridine derivatives are prepared and tested for varieties of biological activities such as, Antifungal [1][2][3] , Antiallergic 4 , Analgesic 5 , Antagonist 6,7 , Antitumor 8 , CNS active agent 9 , Cytotoxic 10 , Inhibitors of cell proliferation 11 , Gastric acid secretion inhibitor 12 , Antimicrobial 13 , Hypolipidemic 14 , Antipyretic 15 etc. In view of getting to synthesized imidazo[1,2-a] pyridines derivatives and evaluated for their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%